Determining the Impact of the Environmental Condition on the Production Performance of Photovoltaic in Kirkuk, Iraq - Abbas, Ehsan Fadhil (New Approaches in Engineering Research Vol. 12, 2021)
The present study investigated the impact of weather conditions on the production performance of the photovoltaic (PV) module. The experiments have been conducted using two identical PV modules of 75 Watt each, and they were placed in the same weather conditions in the summer season in Kirkuk City-Iraq. One of them was used as a conventional module as a reference panel, and the other unit has been used in all required tests. Water circulation has been used to cool the PV module to an excellent soil used to estimate the effect of each hot weather and dust deposition on the performance of PV, respectively. The results show that the fill factor (FF) and PV efficiency affected inversely with temperature increases; on the other hand, the cooling process contributed to increasing the voltage generated across PV panel by 11.8%, while the reduction in voltage generation by unclean panel due to natural pollution deposition on the front of the panel for three months was about 3.8% compared with clean panel and 13.8 % if it has been compared with voltage production by the panel when it has been cooled by water. To improve its performance and be done by periodic maintenance process on the PV module from dust deposition and add the suitable size of PV panels to compensate for the shortfall, which occurs in the power production of the PV unit due to hot weather cannot be controlled.